1947
DOI: 10.1038/bjc.1947.24
|View full text |Cite
|
Sign up to set email alerts
|

A Further Study of the Incidence of Cancer of the Lung and Larynx

Abstract: THE data given below are derived from an examination of the death certificates of cases of cancer of the lung and of the larynx in males from England and Wales for the years 1921 to 1938 inclusive. The figures for the first 12 years of this period (1921 to 1932) were dealt with in an earlier paper (Kennaway and Kennaway, 1936); the material from the subsequent six years has now been INCIDENCE OF CANCER OF LUNG AND LARYNX Factors which may affect the value of the individual death certificate are: (3) Duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
3

Year Published

1954
1954
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 0 publications
0
52
3
Order By: Relevance
“…This occupation group includes craftsmen, foremen, operatives, and laborers in 15 metal industries ranging from blast furnaces, steel works, and rolling mills through various metal machinery and transportation equipment manufacturing industries. As shown in row 2b of 8 Excluded were cases whose assigned exoosure to iron dust was on jobs around metal with descriptions such as, "loading and checking parts," "stock room hauling," "inspector," "maintenance man in plant," "railroad car repairman," "oiler and washer," etc.…”
Section: Results Of Study: Occupational Factorsmentioning
confidence: 99%
“…This occupation group includes craftsmen, foremen, operatives, and laborers in 15 metal industries ranging from blast furnaces, steel works, and rolling mills through various metal machinery and transportation equipment manufacturing industries. As shown in row 2b of 8 Excluded were cases whose assigned exoosure to iron dust was on jobs around metal with descriptions such as, "loading and checking parts," "stock room hauling," "inspector," "maintenance man in plant," "railroad car repairman," "oiler and washer," etc.…”
Section: Results Of Study: Occupational Factorsmentioning
confidence: 99%
“…(1991) Assessment Kennaway and Kennaway (1947) analysed the mortality from cancer of the lung and larynx by occupation in England and Wales in 1921-38 that had been reported earlier (Kennaway & Kennaway, 1936). Data on occupation were obtained from death certificates; the population at risk in each occupation was estimated from national census data, which allowed the calculation of age-adjusted expected numbers of cancers by occupation.…”
Section: Regulations and Guidelinesmentioning
confidence: 99%
“…In the study by Kennaway and Kennaway (1947) Reid and Buck (1956) reported a mortality study of British coke workers, in which deaths among coke plant workers from 1949 to 1954 were identified from the Carbonization Department of the National Coal Board. Causes of death were ascertained either from claims to the trade union's funeral fund that required death certificates, or from the General Registrar's Office.…”
Section: 12mentioning
confidence: 99%
See 2 more Smart Citations